2018
DOI: 10.1002/ajpa.23715
|View full text |Cite
|
Sign up to set email alerts
|

Modern humans sex estimation through dental tissue patterns of maxillary canines

Abstract: ObjectivesDental tissue proportions of human permanent canines is one of only a few sexually dimorphic features that is present in childhood and maintained in adults, offering the opportunity for this to be used in sex determination. This study assesses dental tissue volumes and surface areas of maxillary permanent canines in a sample of known sex to provide new data and to explore the potential of these variables as reliable sexual estimators. Materials and methodsThe teeth studied here derive from 56 individ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
50
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(58 citation statements)
references
References 61 publications
5
50
3
Order By: Relevance
“…Although the degree ranged according to the studied population, previous studies have demonstrated the presence of sexual dimorphism within the human dentition, in which males have larger teeth than females (ZORBA et al, 2011;SABÓIA et al, 2013, PECKMANN et al, 2015GARCÍA-CAMPOS et al, 2018).…”
Section: Discussionmentioning
confidence: 95%
“…Although the degree ranged according to the studied population, previous studies have demonstrated the presence of sexual dimorphism within the human dentition, in which males have larger teeth than females (ZORBA et al, 2011;SABÓIA et al, 2013, PECKMANN et al, 2015GARCÍA-CAMPOS et al, 2018).…”
Section: Discussionmentioning
confidence: 95%
“…The analysis of other dental measurements, such as tissue volumes, has been less common than traditional crown diameters, but dental tissue proportions, tissue volumes, and surface areas have also been identified as being sexually dimorphic (Feeney et al, 2010; García‐Campos, Martinón‐Torres, Martínez de Pinillos, et al, 2018; García‐Campos, Martinón‐Torres, Martín‐Francés, et al, 2018; Harris & Hicks, 1998; Kazzazi & Kranioti, 2017; Saunders, Chan, Kahlon, Kluge, & FitzGerald, 2007; Schwartz & Dean, 2005; Sorenti, Martinón‐Torres, Martín‐Francés, & Perea‐Pérez, 2019; Stroud, Buschang, & Goaz, 1994; Tardivo et al, 2011; Tardivo et al, 2015; Zilberman & Smith, 2001). Despite being used infrequently, the use of dental tissue volumes and surface areas has been recommended for sex determination (García‐Campos, Martinón‐Torres, Martín‐Francés, et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Some evidence exists for sexual dimorphism in enamel thickness (García‐Campos, Martinón‐Torres, Martínez de Pinillos, et al, 2018; García‐Campos, Martinón‐Torres, Martín‐Francés, et al, 2018; Hall, Lindauer, Tufekci, & Shroff, 2007; Sorenti et al, 2019). Overall tooth size, and the sizes of the crown and the root have been found to be larger in males.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall tooth size, and the sizes of the crown and the root have been found to be larger in males. Enamel volume has been found to be larger in females, and consequently it is thought that the enamel does not significantly contribute to overall dental dimorphism (Stroud et al, 1994; Harris and Hicks, 1998; Feeney et al, 2010; García-Campos et al, 2018b; a). Most studies have focused largely on the posterior dentition although recent studies have analysed canine sexual dimorphism (García-Campos et al, 2018a; b).…”
Section: Introductionmentioning
confidence: 99%